Effects of Motion Responses and Drift Forces on Side-by-Side Offloading Operations of FPSO - Patel, M.S.; Liew, M.S.; Mustaffa, Z.; Abdurrasheed, A.S.; Whyte, Andrew (2020)
© 2020, Springer Nature Singapore Pte Ltd. Offloading operations involves transfer of oil or gas from the Floating Production Storage and Offloading system (FPSO’s) to a nearby stationed shuttle tanker. The hydrodynamic interaction between the FPSO and shuttle tanker is an important subject of study. The actual estimate of the vessels behavior is necessary for offloading operation. This paper aims to study the hydrodynamic behavior of side-by-side stationed vessels for offloading operations. The investigation of hydrodynamic behavior is achieved through a diffraction module of ANSYS. The present study includes studying the motion responses and drift forces of side-by-side configured FPSO and shuttle tankers in three different water depth. The obtained results are found consistent with the published work.